The ASEAN Agreement on Trans-boundary Pollution in Relation with Indonesian Haze, Compliance in Theory and Practice - Roesa, Nellyana (Indonesian Journal of International Law, 2012)
The trans-boundary pollution has become a major issue within the Association of Southeast Asian Nations (ASEAN) when the forest fi res took place in Indonesia. Indonesia’s neighboring countries had to face problems dealing with the smoke and haze that spread into their territories. ASEAN Member States’ attempts to combat the smoke and haze problem depicted on Agreement on Trans-boundary Haze Pollution (Haze Agreement), which up to now Indonesia has been the only State that has not ratified the agreement. The reluctance of Indonesia to ratify the agreement becomes a problem to the enforcement. It is contrary to the argument that the ratification is believed to bring some benefits for Indonesia from transfer of knowledge and technology and also from research. While Haze Agreement requires cooperation among ASEAN Member States to reach the objectives of the agreement, the cooperation itself is not limited to the participation of the whole members at the same time, but also possible to conduct such cooperation in form of bilateral effort or other kind of accepted by the parties. With some flexibilities offered by the Haze Agreement, the effectiveness of the agreement does not rely only on the commitment shown by the ratification of ASEAN Member States to the agreement, but also relies on the level compliance that shown by their effort to combat the possibility of upcoming trans-boundary pollution matters within the region.